Effect of co-culture of Komagataeibacter nataicola and selected Lactobacillus fermentum on the production and characterization of bacterial cellulose. (1st January 2023) - Jiang, Huanyuan; Song, Zeming; Hao, Yaofei; Hu, Xiaoping; Lin, Xue; Liu, Sixin; Li, Congfa
Abstract: Using pre-fermented coconut water brings about a high yield of bacterial cellulose (BC) from Komagataeibacter strains in food industry, but the production is unstable and even risky. Therefore, finding a controllable and high-yield production mode of BC is necessary. Our previous study has showed that Lactobacillus is one of the dominant genera in pre-fermented coconut water. Based on this, the effect of co-culture of K. nataicola and 17 coconut-sourced Lactobacillus spp. strains on the production of BC was investigated in this study. Results suggested that co-culture of K. nataicola and Lactobacillus spp. strains had varied effects on the production of BC. Co-culture of K. nataicola Q2 and L. fermentum SR can effectively improve the production of BC via affecting the formation of β-1, 4-glucan chains and crystallization of microfibrils. Moreover, direct and indirect pathways were involved in promoting the formation of β-1, 4-glucan chains in the co-culture system. The co-culture of K. nataicola Q2 and L. fermentum SR led to the production of BC membrane with higher crystallinity but lower thermal degradation, hardness, adhesiveness, and water holding capacity. This research provides a reference for realizing controllable increase of BC production and modification of BC. Highlights: Co-culture of K. nataicola and Lactobacillus strains variedly affected BC yield. Co-culture of K. nataicola Q2 and L. fermentum SR enhanced BC yield by up to 4.5 folds. Co-culture with L. fermentum SR promoted BC synthesis via two pathways. Co-culture with L. fermentum SR increased BC crystallinity. Co-culture with L. fermentum SR changed the texture profile and WHC of BC.